2015
DOI: 10.15386/cjmed-505
|View full text |Cite
|
Sign up to set email alerts
|

The role of hormones in the pathogenesis of psoriasis vulgaris

Abstract: Psoriasis vulgaris is a chronic, common skin disease, which affects the patient’s quality of life to the highest degree. Several exogenous factors and endogenous hormonal changes may act as triggers for psoriasis.The skin possesses a true endocrine system, which is very important in multiple systemic diseases. A number of conditions are associated with psoriasis, and its severity can also be influenced by hormones. Even though the sex hormones and prolactin have a major role in psoriasis pathogenicity, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 109 publications
1
22
0
4
Order By: Relevance
“…In the present study, the high frequency of psoriasis attack was among males rather than females, this may be due to the hormonal differences between them [25,26], and in turn, their effect on immune response [27], consequently males tend to provoke more T-helper cells which have a proinflammatory role in inducing or development of psoriasis to become severe incidence [28].…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…In the present study, the high frequency of psoriasis attack was among males rather than females, this may be due to the hormonal differences between them [25,26], and in turn, their effect on immune response [27], consequently males tend to provoke more T-helper cells which have a proinflammatory role in inducing or development of psoriasis to become severe incidence [28].…”
Section: Resultsmentioning
confidence: 53%
“…The results clarified that the age was ranged between 20-60 years and the mean age for psoriasis was 42.8±2.0. The results recorded that most psoriasis patients (52.08 %) were within the second and third decades (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) year, while the lowest percentages were in (51-65) year. This results were in agreement with [19,20], who indicated that the age of psoriatic patients was within the second and third decades.…”
Section: Resultsmentioning
confidence: 98%
“…It is well known that the nervous system, the endocrine system and the skin have the same embryological origin, from the ectoderm [86]. Also, the function and the normal development of the skin are influenced by hormones, among them sex hormones, thyroid hormones or stress hormones [87].…”
Section: Endocrine Assessment In Psoriasismentioning
confidence: 99%
“…For example, the thyroid hormones, triiodothyronine (T3) and free thyroxine (T4) cause an increase in the Epidermal Growth Factor (EGF) which leads to epidermal hyperplasia, also determining the proliferation of keratinocytes (3), an aspect commonly found in psoriasis vulgaris. On the other hand, sexual hormones, such as estrogens, modulate the immune responses: either by decreasing the psoriatic inflammation or by stimulating the proliferation at keratinocyte level (4). Prolactin (PRL), a pituitary hormone involved in lactation and reproduction has also been mentioned as an important immune modulator (5).…”
Section: Introductionmentioning
confidence: 99%